BENDERA TAUHID DALAM PANDANGAN SEMIOTIKA C.S. PIERCE - MISBAH PRIAGUNG NURSALIM (PIKTORIAL : Journal of Humanities, 2019)
Flags are a symbol of a group that becomes a sacred marker. Even though it forms a sign, the image cannot be considered as a sign, but has a high philosophical value that makes the owner willing to struggle to maintain the symbol. Research has a high urgency value because Indonesian people still consider all symbols that have sacred values and are still on average all types of symbols. The data in this study is a flag that reads tawhid pronunciation. Qualitative semiotic methods are interpretive in analyzing data and using semiotic theory C.S. Pierce as a surgical instrument. The result, not all monotheistic memorization has the same meaning. That is because each flag has a different history and philosophy.Keywords: flag, monotheism, semiotics